STRATEGI PENCEGAHAN STUNTING MELALUI KELOMPOK JAMA’AH YASIN DALAM PENGENALAN MATABA (MAKANAN TAMBAHAN BALITA) - Faizah Faizah; Aliyahuna Nafisa Dya K.D; Eka Mahargiani Rokhma (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
Stunting which is currently a social problem, is caused by unbalanced nutrition for toddlers. The principle of low parental understanding of balanced nutrition patterns for children, as well as the dual role of parents as housewives as well as careers so that they are forced to entrust children to parents (grandmothers), the majority of whom are still ancient and do not understand parenting strategies. This then became the author's concern to examine more deeply the stunting prevention strategy through the Jamaa'ah Yasin in the introduction of additional food for toddlers (MATABA). Jama'ah Yasin here is a group of young to middle-aged mothers who are dominated by the background of caring for toddlers. This assistance uses the PAR method with Community social research and problem diagnostic steps, Community strategic planning, Political Action, and reflection. The results of the service start from observations of data collection about the causes of stunting, FGD with the Yasin congregation to determine strategies, socialization of the introduction of additional food, cooking demonstrations, to making MATABA pocketbooks and reflection.